Analisis Kompetensi dan Kompensasi terhadap Kinerja Karyawan Berbasis Lingkungan Kerja Non Fisik - Siti Kusandhitasari Jayaningrum; Kusuma Chandra Kirana; Gendro Wiyono (Jurnal Bingkai Ekonomi (JBE), 2020)
The research aims to analyze: (1) the effect of competence on performance, (2) the effect of compensation on performance, (3) the influence of non-physical work environment on performance, (4) non-physical work environment moderates the effect of competence on performance, and (5) non-physical work environment moderates the effect of compensation on performance. This research is quantitative with a survey method. The data collection uses a questionnaire with validity and reliability tests. The data analysis methods are descriptive and inferential. The results of the study for significance of 5%: (1) competence influences performance with P Values = 0.001, (2) compensation influences performance with P Values = 0.033, (3) non-physical work environment has no effect on performance because P Values = 0.168, (4) non- physical work environment does not moderate the effect of competence on performance because P Values = 0.797 and Original Sample (O) = 0.038, (5) non-physical work environment does not moderate the effect of compensation on performance because P Values = 0.325 and Original Sample (O) = -0.099.